Intelligent Personal Supercomputer for Solving Scientific and Technical Problems - Khimich, O.M.; Molchanov, I.M.; Mova, V.I.; Nikolaichuk О.O.; Popov, O.V.; Chistjakova, T.V.; Yakovlev, M.F.; Tulchinsky, V.G.; Yushchenko R.А. (Science and Innovation, 2024)
New domestic intelligent personal supercomputer of hybrid architecture Inparkom_pg for the mathematical modeling of processes in the defense industry, engineering, construction, etc. has been designed. Software for the automatic research and tasks of computational mathematics with approximate data of different structures has been developed. Applied software to provide mathematical modeling problems in construction, welding, and filtration processes has been implemented.